2012
DOI: 10.1186/1475-2840-11-146
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis reveals gender-specific predictors of cardiometabolic risk in 6th graders

Abstract: BackgroundThe purpose of this study was to determine the sex-specific pattern of pediatric cardiometabolic risk with principal component analysis, using several biological, behavioral and parental variables in a large cohort (n = 2866) of 6th grade students.MethodsCardiometabolic risk components included waist circumference, fasting glucose, blood pressure, plasma triglycerides levels and HDL-cholesterol. Principal components analysis was used to determine the pattern of risk clustering and to derive a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…16 PCA can be effectively used in pediatric cohorts to aid the interpretation of statistical component clustering, 17 as well as for identifying behavioral predictors of risk. Although previous studies have incorporated similar continuous scores to improve robustness of cardiometabolic risk assessment in pediatric research, 18 the PCA method also calculates the respective "weight" (ie, the loading coefficient) of each component on absolute cardiometabolic risk.…”
mentioning
confidence: 99%
“…16 PCA can be effectively used in pediatric cohorts to aid the interpretation of statistical component clustering, 17 as well as for identifying behavioral predictors of risk. Although previous studies have incorporated similar continuous scores to improve robustness of cardiometabolic risk assessment in pediatric research, 18 the PCA method also calculates the respective "weight" (ie, the loading coefficient) of each component on absolute cardiometabolic risk.…”
mentioning
confidence: 99%
“…No guidelines are given regarding passive smoking, although this may be relevant for children, since childhood exposure to tobacco smoke leads to endothelial dysfunction in both children [101] and young adults [102]. Although we did not find evidence for a synergistic effect of smoking and childhood obesity on endothelial dysfunction, maternal smoking has been shown to correlate with several obesityrelated risk factors in young children [103]. Gender matters in childhood since it influences endothelial function, with FMD being lower in boys [104].…”
Section: Flow-mediated Dilationmentioning
confidence: 59%
“…Exercise capacity and HRR were detected to be significantly impaired in young adult males with MS, by Deniz et al [21]. It was indicated in the literature that exercise training induced favorable changes in HRR in obese men with MS [22], while reduced exercise capacity was related to cardiometabolic risk factors even in young populations [23]. Furthermore, it was shown that there was a relationship between MS and cardiac autonomic dysfunction, as detected by HR turbulence in non-diabetic patients [24].…”
Section: Discussionmentioning
confidence: 99%